Chicago 10 [videorecording (DVD)] - Morgen, Brett; Azaria, Hank, 1964-; Baker, Dylan; Nolte, Nick (Paramount Home Entertainment, 2008)
A look at what happened during the anti-war protest of the 1968 Democratic National Convention in Chicago, and the subsequent trail brought against the protest organizers by the city. Includes animation, archival footage, and music from today's artists.